Macroethnic groups in the Andean area - Rostworowski, María (1990)
In times prior to the Inca domain, that is, during the Late Intermediate period, the Andean area was made up in the political aspect, by numerous macro-ethnic groups. Of all the Señoríos, the Chimú one stood out above the others for its territorial extension that, during its peak, occupied the valleys from Huarmey to Piura and Tumbes. Research on the indigenous past forces us to try to outline what the macro-ethnic groups were.